2005
DOI: 10.1016/j.neuropharm.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

NMDA-induced potentiation of mGluR5 is mediated by activation of protein phosphatase 2B/calcineurin

Abstract: Previous reports have shown that activation of N-methyl-D-aspartate (NMDA) receptors potentiates responses to activation of the group I metabotropic glutamate receptor mGluR5 by reversing PKC-mediated desensitization of this receptor. NMDA-induced reversal of mGluR5 desensitization is dependent on activation of protein phosphatases. However, the specific protein phosphatase involved and the precise mechanism by which NMDA receptor activation reduces mGluR desensitization are not known. We have performed a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…There are data showing that activation of NMDA receptors may lead to activation of calcineurin that in turn may modulate mGluR5 function by dephosphorylating mGluR5 at sites that are phosphorylated by PKC on the C-terminal tail of the receptor (Alagarsamy et al, 2005;Gereau and Heinemann, 1998). Moreover, it has been reported that a single administration of PCP in rats resulted in a decrease in the mGluR5 mRNA expression in the hippocampal formation and in a number of subcortical regions (Abe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are data showing that activation of NMDA receptors may lead to activation of calcineurin that in turn may modulate mGluR5 function by dephosphorylating mGluR5 at sites that are phosphorylated by PKC on the C-terminal tail of the receptor (Alagarsamy et al, 2005;Gereau and Heinemann, 1998). Moreover, it has been reported that a single administration of PCP in rats resulted in a decrease in the mGluR5 mRNA expression in the hippocampal formation and in a number of subcortical regions (Abe et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that mGluR5 can modulate the NMDA receptor function at the molecular and cellular level (Awad et al, 2000;Brakeman et al, 1997;Doherty et al, 1997). Further, the opposite direction of this modulation has been reported as well, thereby suggesting a reciprocal positive-feedback interaction between these two receptor subtypes (Alagarsamy et al, 1999(Alagarsamy et al, , 2005Luthi et al, 1994). Importantly, at the behavioral level, antagonists of the mGluR5 have been found to potentiate the effects of NMDA receptor antagonists in several tests including prepulse inhibition (PPI) of the startle response, locomotor activity, memory tasks, and unilateral 6-OHDA-lesion model (Henry et al, 2002;Homayoun et al, 2004;Kinney et al, 2002;Turle-Lorenzo et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…By dephosphorylating the receptor, CaN can prolong its activity after glutamate release ( Fig. 1; Alagarsamy et al 2005). This effect of CaN is likely important for the induction of LTD, some forms of which rely on mGluR5 in the hippocampus (Camodeca et al 1999;Sung et al 2001;Huang and Hsu 2006;Naie et al 2007;Neyman and Manahan-Vaughan 2008).…”
Section: Other Receptors and Channels Targeted By Canmentioning
confidence: 99%
“…Due to the global distribution and rapid synaptic transmission of the NMDAR, it is not suited as a therapeutic target as its effects are widely excitotoxic (Ellenbroek, 2012). However mGluR5 and NMDAR are connected by a scaffolding link (Tu et al, 1999) and are known to functionally interact, particularly in the PFC (Pisani et al, 2001;Alagarsamy et al, 2002Alagarsamy et al, , 2005Benquet et al, 2002;Homayoun and Moghaddam, 2006). Hence, mGluR5 is of current interest as a novel therapeutic target for the treatment of schizophrenia.…”
Section: Mglur5 Binding Density and Protein Levels Are Unaltered In Tmentioning
confidence: 99%